Efficacy and safety of curcumin in psoriasis: preclinical and clinical evidence and possible mechanisms - Zhang, Shuo; Wang, Jiao; Liu, Liu; Sun, Xiaoying; Zhou, Yaqiong; Chen, Siting; Lu, Yi; Cai, Xiaoce; Hu, Manqi; Yan, Ge; Miao, Xiao; Li, Xin (Frontiers in Pharmacology, 2022)
Background: Psoriasis is a chronic and immune-mediated inflammatory skin disease. Many studies have shown that curcumin (CUR) has strong anti-inflammatory effects and can improve psoriasis; however, its efficacy and safety have not been confirmed, and the specific mechanism remains to be elucidated. Objective: To evaluate the efficacy, safety, and possible mechanisms of CUR in the treatment of psoriasis. Methods: The Cochrane Library, Embase, PubMed, Web of Science, China National Knowledge Infrastructure, Wanfang, and VIP (China Science and Technology Journal Database) were systematically searched for clinical trials and preclinical studies on the use of CUR in psoriasis treatment. All databases were searched from inception to January 2022. The meta-analysis was performed using RevMan 5.3 software. Results: Our meta-analysis included 26 studies, comprising seven clinical randomized controlled trials and 19 preclinical studies. A meta-analysis of clinical trials showed that both CUR monotherapy and combination therapy improved Psoriasis Area and Severity Index (PASI) scores in patients compared to controls (standard mean difference [std.MD]: −0.83%; 95% confidence interval [CI]: −1.53 to 0.14; p = 0.02). In preclinical studies, CUR showed better performance in improving the phenotype of psoriatic dermatitis mice compared to controls, including total PASI score (std.MD: 6.50%; 95% CI: 10.10 to −2.90; p = 0.0004); ear thickness (p = 0.01); and the expression of inflammatory cytokines such as interleukin (IL)-17, tumor necrosis factor (TNF)-α, IL-17F, and IL-22 (p < 0.05). In cell studies, CUR inhibited cell proliferation (p = 0.04) and the cell cycle (p = 0.03) and downregulated the inflammatory cytokines IL-6 and IL-8 (p < 0.05). Conclusions: CUR has excellent efficacy and broad potential to treat psoriasis in multiple ways. Its use also plays a crucial role in improving the psoriasis phenotype and reducing the inflammatory microenvironment. In conclusion, our findings suggest that CUR alone or in combination with other conventional treatments can effectively treat psoriasis.